Content Based Image Retrieval System - Dahiya, Kajol; Gautam, Gaurav (International Journal of Computer Sciences and Engineering, 2019)
This paper proposes a new classifier named Extreme Learning Machine (ELM) on a hybrid framework for developing a Content Base Image Retrieval (CBIR) system to improve the accuracy problems faced with the earlier image retrieval system. This system mainly aims towards the accuracy with less consumption of time. In this system, Wang database is used with Local Binary Pattern (LBP), color moment, canny edge and region props for the extraction of texture, color, edge and shape feature respectively. After extracting all the features from the image, distance matrix will be determined to use it for further implementation. And then ELM classifier is used in this proposed CBIR to categorize all the images. Score Level Fusion is used as similarity measure for finding similar images. The obtained results proved that the accuracy and efficiency of CBIR system increased at a very high rate after using ELM classifier in terms of precision, recall, f-measure and retrieval time than just using similarity measure of the extraction features. The elapsed time and the average precision value is 0.277391 and 97.2500 respectively which is much accurate than the state-of-the-art techniques.